Seasonal Variations of the Mercury Multiple Isotopic Compositions of Subrural and Urban Aerosols Highlight an Additional Atmospheric Hg0 Oxidation Pathway - AuYang, David; Chen, Jiubin; Zheng, Wang; Lang, Yunchao; Wang, Yina; Wang, Zhongwei; Zhang, Yuanyuan; Liu, Yulong; Zhang, Ke; Cai, Hongming; Yuan, Wei; Widory, David (Frontiers in Environmental Science, 2022)
The mechanisms triggering the large variations in the mercury (Hg) multiple isotopic compositions of atmospheric particle-bound Hg worldwide still remain unclear. The comparison of Hg isotopic compositions in aerosols collected in urban and rural areas may help distinguish the effects of natural processes from those of anthropogenic inputs. We thus investigated the Hg isotopic compositions of PM10 aerosols collected seasonally during 2015 at two monitoring stations on Montreal Island, one located downtown and the other in its westernmost subrural part, barely impacted by the city anthropogenic emissions. Our results show that, while Hg isotopic compositions present no seasonality at the urban station, possibly due to constant anthropogenic emissions, the subrural samples display clear seasonal variations, with higher Δ199Hg and Δ200Hg values (up to 0.77‰ and 0.12‰, respectively) during summer and close to 0‰ during the rest of the year, that cannot solely be explained by anthropogenic primary emissions. Besides, Δ200Hg measured in the subrural aerosols display a positive correlation with O3 suggesting the implication of secondary processes involving ozone. We propose that the significant summer shift in the multiple Hg isotopic compositions may reflect a transition in the corresponding Hg0 oxidation pathway, from halogens-triggered to ozone-dominated reactions. Still, this hypothesis needs to be further tested. Nevertheless, it demonstrates that Hg isotopes are effective at characterizing secondary processes that control its atmospheric budget, even at a local scale (i.e., urban vs subrural) and could thus be used to better constrain its atmospheric chemistry in various environments.